High-resolution wide-range dynamic neutron monochromators. (10th April 2015) - Girolami, M.; Pietropaolo, A.; Bellucci, A.; Calvani, P.; Trucchi, D. M.
Abstract: This work proposes the concept of a high-resolution wide-range dynamic neutron monochromator able to operate up to a few eV, thus significantly extending the reliable operating neutron energy range of the state-of-the-art crystal-based devices, and to improve energy resolution in the epithermal range if compared to mechanical choppers. The proposed device is based on a radiation-hard aluminium nitride (AlN)/diamond heterostructure, operating as a super-high-frequency (> 3 GHz) high-speed (> 10000 m/s) acoustic resonator. The resulting surface acoustic wave (SAW) acts as a dynamic grating for the incoming neutrons: as long as neutron speed is lower than (or at least comparable to) SAW speed, diffraction angles are significantly enhanced, thus allowing for neutron beam monochromatization to be effective up to the eV energy range. SAW amplitude can be electrically tuned to increase first-order reflectivity, leading to an enhanced intensity of the monochromatized beam.